The outcomes of Perthes’ disease: Development of a core outcomes set for clinical trials in Perthes’ disease - Leo, DG; Jones, H; Murphy, R; Leong, WY; Gambling, T; Long, A; Laine, J; Perry, D (British Editorial Society of Bone and Joint Surgery, 2020)
Aims To identify a suite of the key physical, emotional, and social outcomes to be employed in clinical practice and research concerning Perthes' disease in children.